Learning Doesn't Have to Be About Sitting Still: The Revolution of Active Learning in Elementary Schools Through Outdoor Learning Methods - Rosmaria, Rosmaria; Mamonto, Samuel (Ludi Litterarri, 2025)
This study examines the application of outdoor learning methods as an alternative to learning in elementary schools that have been dominated by passive conventional methods. Conventional methods that focus on lectures and written assignments have proven to be less effective in encouraging active involvement, creativity, and the development of 21st-century skills such as critical thinking and collaboration. Outdoor learning offers a dynamic learning paradigm with direct experience outside the classroom, which not only increases students' motivation and conceptual understanding, but also strengthens social skills and environmental awareness. This approach allows for cross-disciplinary integration and contextual learning that is relevant to the needs of the 21st century. The study used a descriptive qualitative approach with observations, interviews, and documentation studies on teachers, students, and principals who have implemented outdoor learning. The results show that outdoor learning is able to improve the quality of learning through meaningful real experiences, strengthen students' emotional and cognitive involvement, and support the development of soft skills. However, challenges in the form of compiling assessment indicators and limited facilities need to be overcome. In conclusion, outdoor learning is an innovative pedagogical strategy that is effective in preparing students to become holistic individuals who are adaptive and ecologically and socially responsible...